(untitled) (The Peerian Journal, 2023)
The Design is one of these arts and the most applied to all activities aimed at organizing and forming things, as it is an essential work for a person because most of the things he does include an aspect of design, which is one of the important technical and cultural foundations. An integrated plan to form something and install it into a unified template from a functional and aesthetic point of view. Advertising represents one of the specialized areas, and it is considered one of the most important and effective means of media to introduce customers and consumers to the types and advantages of different commodities, in addition to being an art that works to attract and tempt the consumer to prefer a commodity or accept a certain idea over others . Talking about advertising as an important means of promoting commodities is no longer just words arranged for a simple meaning. Advertising has become a self-contained science, and its means have become diverse, wide, and directed to the segments of society carefully and accurately in a way that achieves the primary goal of advertising